2019
DOI: 10.1111/jnc.14876
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal NLRC5 regulates MHC class I expression in Neuro‐2a cells and also during hippocampal development

Abstract: Major histocompatibility Complex class I (MHC I) molecules are ubiquitously expressed, being found in most nucleated cells, where they are central mediators of both the adaptive and innate immune responses. Recent studies have shown that MHC I are also expressed in the developing brain where they participate in synapse elimination and plasticity. Up‐regulation of MHC I within the developing brain has been reported, however, the mechanism(s) regulating this developmental up‐regulation of neuronal MHC I remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 44 publications
3
19
0
Order By: Relevance
“…signaling cascade relied on activation of the MAPK pathway (Lv et al, 2015). We also confirmed that NLRC5, but not CIITA, was broadly expressed in the mouse brain and promoted MHC-I expression in hippocampal neurons (Li et al, 2020). In this study, we analyze the regulation of MHC-I expression from a new perspective: regulation by miRNAs in hippocampal neurons, adding new information regarding the tight and complex regulatory system that controls classical MHC-I molecule levels during the development of the hippocampus.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…signaling cascade relied on activation of the MAPK pathway (Lv et al, 2015). We also confirmed that NLRC5, but not CIITA, was broadly expressed in the mouse brain and promoted MHC-I expression in hippocampal neurons (Li et al, 2020). In this study, we analyze the regulation of MHC-I expression from a new perspective: regulation by miRNAs in hippocampal neurons, adding new information regarding the tight and complex regulatory system that controls classical MHC-I molecule levels during the development of the hippocampus.…”
Section: Discussionmentioning
confidence: 58%
“…After completing their functions, protein abundance becomes significantly reduced with age until neuronal MHC-I proteins can no longer be detected after P60. In contrast, mRNA expression is gradually increased from P0 to P60 after which it remains relatively stable (Liu et al, 2013;Li et al, 2020). A similar expression pattern of MHC-I proteins is observed during human CNS development (Zhang et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations